Optimizing Finance for Development - Cordella, Tito (World Bank, Washington, DC, 2018)
The World Bank Group recently adopted the "cascade framework" to "maximize finance for development." The cascade recommends that reforms be tried first, followed by subsidies, and then public investments. To understand the economics of the cascade, this paper presents a model where reforms, subsidies, and public investments can be used to fill the investment gap, and computes the welfare associated with their different sequencing. The cascade is optimal when reforms increase efficiency at no cost. When they are costly, if policies can be project specific, their sequencing does not matter; if not, the cascade can be optimal if agents are myopic, but not if they are forward-looking. Tensions may thus arise between maximizing private financing and optimizing financing for development.